A Comparative Study on Efficacy and Safety of Methotrexate Versus Apremilast in the Management of Chronic Plaque Psoriasis: Tertiary Care Center Based Interventional Study - Aryal, Alisha; Bhattarai, Niraj; Poudel, Ramesh Sharma; Jha, Smita; Shris, Nupendra (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Introduction: Psoriasis is a common skin presentation in dermatology OPD. Methotrexate and apremilast are frequently used for the management of chronic plaque psoriasis. Objectives: To compare the efficacy and safety of methotrexate versus apremilast for the management of chronic plaque psoriasis Materials and Methods: This was an interventional study conducted among 41 patients. The patients were divided into 2 groups. Group A received apremilast 10-30mg twice daily, and group B received methotrexate 10-15mg once weekly for 16 weeks. The patients were evaluated at 4, 8 and 16 weeks. PASI score, DLQI score and adverse effects were documented in every follow-up. Results: The PASI score significantly reduced from 17.22 ± 8.61 (baseline) to 3.90 ± 2.92 (16 weeks) in group A and 18.64 ± 9.02 (baseline) to 5.95 ± 2.89 (16 weeks) in groups B (P = < 0.001). At 16 weeks, the mean PASI score (3.90 ± 2.92) in group A was significantly less than group B (5.95 ± 2.89) (P = 0.02). The percentage reduction of mean PASI from baseline to 16 weeks was 77% in group A and 68.07% in group B. PASI 75 was achieved by 11 patients (52.30 %) in group A and 8 patients (40 %) in group B at 16 weeks. Both groups had a significant decrease in DLQI as compared to baseline at 16 weeks, with insignificant differences between the two groups during each visit. No severe side effects were seen in both groups. Conclusion: Both treatments can be considered in treating chronic plaque psoriasis. However, apremilast showed more efficacy than methotrexate.